Secondary school geography teachers' perceptions of the role of environmental education in geography with particular reference to Natal Education Department teachers - Wassermann, Johannes Michiel (Rhodes University, Faculty of Education, Department of Education, 1995)
Environmental Education (EE) as a development cannot be ignored by Geography or Geographers particularly since South Africa, as the rest of the world, is confronted by a looming environmental crisis. Geography is an environmental science concerned primarily with man-environment relationships using an environmental approach to develop the skills, knowledge, values and attitudes necessary for sustainable living. Geography has a vital role to play in addressing environmental issues. In formal education Geography teachers will be responsible for the implementation of such an approach. This study therefore investigates the perceptions of Natal Senior Secondary School Geography teachers regarding the role of EE in Geography. Questionnaires and semi-structured interviews were used to determine this. The study revealed that although these teachers are well qualified and motivated they had a limited grasp of the theory underpinning current EE and Geographical thinking. Recommendations are made for the development of an environmental approach in the teaching of Geography.
Keywords: Geography teachers -- South Africa -- KwaZulu-Natal -- Attitudes; Environmental education -- South Africa -- KwaZulu-Natal